Employee Performance in The Hospitality Sector: The Roles of Human Relations, Work-Life Balance, And Individual Characteristics - Ni Kadek Sudiartini; I Gede Rihayana; Bagus Nyoman Kusuma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
This study aims to examine the influence of human relations, work-life balance, and individual characteristics on employee performance at New Moon Cafe Kedonganan. The study population consisted of all 35 employees at New Moon Cafe Kedonganan. The sample was determined using a saturated sample, resulting in a sample of 35 employees. The data collection methods used in this study were observation, document analysis, interviews, and questionnaires. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that human relations have a positive and significant effect on employee performance at New Moon Cafe Kedonganan, work-life balance has a positive and significant effect on employee performance at New Moon Cafe Kedonganan, and individual characteristics have a positive and significant effect on employee performance at New Moon Cafe Kedonganan.